Synchronic and Diacronic Analysis of the Word Zauj in the Al-Qur'an/ Analisis Sinkronik dan Diakronik Kata Zauj Dalam Al-Qur’an - Ummu Hani Assyifa; Mirwan Akhmad Taufiq (Journal of Arabic Language Studies and Teaching, 2021)
Abstract A single word in the Qur’an may give many similar and sometimes different meanings. Determining the intended meaning of the verse has become a necessary matter. This research attempts to discover the different meanings of the word “Zauj” written in the texts of the Holy Qur’an and to discover the development of the meaning of “Zauj” throughout history; pre-Quranic, during the revelation, pasca-Quranic. This research uses both quantitative and qualitative methods using synchronic and diachronic analysis techniques. The primary data used is the word Zauj in the Qur’an and the secondary data use all related articles, especially the Tafsir al-Misbah. The results show that the word Zauj has six different meanings; husband, wife, couple, kind of plants, kind of animals, and kind of a group. And its meaning before Islam may refer to the mattress that protects from the weather. Its meaning in the modern period is divided into classical, medieval and modern ones.